Calcium carbonate (CaCO3) production of a subpolar rhodolith bed: Methods of estimation, effect of bioturbators, and global comparisons. (5th September 2020) - Teed, Laura; Bélanger, David; Gagnon, Patrick; Edinger, Evan
Abstract: Rhodolith beds are major biogenic calcium carbonate producers, with production rates that can be similar to those of coral reefs. Production rates vary latitudinally because of differences in abiotic and biotic drivers, but the different methods used to estimate CaCO3 production rate may also explain some of the wide variation among estimates. We used a 378-day manipulative experiment in a subpolar Newfoundland rhodolith bed to: (1) quantify and compare gross and net rhodolith CaCO3 production rates; (2) compare production estimates derived from branch extension and weight change methods; and (3) test the hypothesis that bioturbators increase rhodolith branch extension [growth] and CaCO3 production. We also reviewed published estimates of CaCO3 production rates in rhodolith-forming, coralline red algae from polar to tropical realms to place our findings within a global context. Gross (806.1 g CaCO3 m −2 y -1 ) and net (196.2 g CaCO3 m −2 y −1 ) rhodolith CaCO3 production rates estimated from rhodolith weight change and rhodolith density (individuals m −2 ) in the bed were similar to those in European beds and lower than in subtropical and tropical beds. The latter net production rate was lower than carbonate production estimated from rhodolith biomass (g m −2 ) in the bed divided by calculated rhodolith age (based on branch extension rate and physical dimensions, 325.7 g CaCO3 m −2 y −1 ). Rhodolith minimum age estimates ranged from 35.8 y (based on use of the branch extension method), to 37.9 y (gross weight change) to 115.1 y (net weight change), indicating that different methods can under- or over-estimate age by up to three times. Bioturbators, known to affect sediment load, did not affect branch extension rate (0.541 mm y −1 ) or weight change (1.64 g y −1 ) of live, stained, or unstained rhodoliths. Our results imply that gross CaCO3 production by living rhodoliths is far greater than net estimates, in which dry weight loss by dead rhodoliths may account for as much as 75% of gross production. CaCO3 production rates reported in the present study are similar to other rhodolith beds in the polar and subpolar carbonate realms, but there is a marked discrepancy among studies because of the variety of methods of estimation used. Graphical abstract: Image 1 Highlights: Bioturbators did not affect Newfoundland rhodolith extension or CaCO3 production. CaCO3 production in Newfoundland rhodolith beds resemble other subpolar bed rates. Weight loss in dead rhodoliths may account for as much as 75% of gross production. Rhodolith weight change and extension not correlated; yield similar production rates. Disparity among studies using varying methods estimating rhodolith CaCO3 production.